Discrimination and coloniality in Rafael Correa's Ecuador (2007-2017); Discriminación y colonialidad en el Ecuador de Rafael Correa (2007-2017) - Martínez Novo, Carmen (Universidad Autónoma Metropolitana, 2018)
Two forms of discrimination against indigenous people in Ecuador are examined: ventriloquism, when non-indigenous people speak on behalf of indigenous people; and public racism, when State authorities use repression based on the humiliations practiced in their colonial past. The example of ventriloquism discussed is the concept of good living, or Sumak Kawsay, during Rafael Correa’s government. The examples of public racism are taken from the repressive practices of the security forces of the regime. This article also reflects on the role of some decolonial scholars in informing and promoting the policies of the government of Rafael Correa towards indigenous peoples and the environment. It is argued that while these academics have called the regime decolonial, its ventriloquist and repressive practices are based on a repertoire with deep colonial roots.; Se examinan dos formas de discriminación contra los indígenas en Ecuador: la ventriloquía, cuando los no indígenas hablan por los indígenas, y el racismo pú blico, cuando las autoridades del Estado usan formas de represión basadas en humillaciones típicas del pasado colonial o de la hacienda. El ejemplo de ventriloquía discutido es el concepto de buen vivir o sumak kawsay en el gobierno del presidente Rafael Correa. Los ejemplos de racismo público se toman de las prácticas represivas de las fuerzas de seguridad del régimen. Se ofrece una reflexión sobre el papel que han jugado algunos académicos de la llamada inflexión decolonial en asesorar y promover las políticas del régimen de Correa hacia los pueblos indígenas y el medio ambiente. Se sostiene que mientras estos académicos han llamado al régimen de Correa decolonial,